The Influence of Digital Literacy on the Use of Whatsapp Group Applications for Students and Teachers: Pengaruh Literasi Digital Terhadap Penggunaan Aplikasi Grup Whatsapp Bagi Siswa dan Guru Di SMKS Muhammadiyah 9 Medan - Siregar, Dahris; Harahap, Faisal Sadat; Sitepu, Karolina; Adlina, Min; Sabila, Puji Chairu; Prasetyo, Andi; Rivai, Muhammad; Nababan, Samuel; Br. Silalahi, Dita Regina (CONSEN: Indonesian Journal of Community Services and Engagement, 2024)
The process of data prevention and filtering is necessary because the development and advancement of the internet has led to excessive use of technology by students. Through counseling or socialization from community observers about current conditions and situations that can have a bad impact and bring many losses to adolescents, which will definitely interfere with their mental health and productivity as adolescents. As a result, counselling and mentorship are the goals of carrying out this service projec. teaching the people, especially vocational students about the impact of digital literacy on the smart and wise use of the WhatsApp group application by students and teachers. Lecture, discussion, and simulation methods are used to carry out this activity as counseling. 32 students from SMKS Muhamamdiyah 9 Medan became participants. The results of counseling activities show that students are very proficient in digital literacy. Not only has moral awareness in communicating, but also has beneficial skills to receive, create, and disseminate information. Pupils can recognise when to utilise WhatsApp as a learning tool to communicate between teachers and students. This was shown by partners how important short information collected through the WhatsApp application is to make people use social media intelligently without misusing it, starting with themselves. The WhatsApp application is very important to provide knowledge to participants and help teachers and students provide and get learning information. It can also be shared with friends, companions, family and other close people